Protocols for hyperlactatemia induction in the lactate minimum test adapted to swimming rats - de Araujo, Gustavo Gornes [UNESP]; Papoti, Marcelo [UNESP]; Manchado, Fulvia de Barros [UNESP]; Rostorn de Mello, Maria Alice [UNESP]; Gobatto, Claudio Alexandre [UNESP] (Elsevier B.V., 2007)
The lactate minimum test (LACmin) has been considered an important indicator of endurance exercise capacity and a single session protocol can predict the maximal steady state lactate (MLSS). The objective of this study was to determine the best swimming protocol to induce hyperlactatemia in order to assure the LACmin in rats (Rattus norvegicus), standardized to four different protocols (P) of lactate elevation. The protocols were PI: 6 min of intermittent jumping exercise in water (load of 50% of the body weight - bw); P2: two 13% bw load swimming bouts until exhaustion (thin); P3: one thin 13% bw load swimming bout; and P4: two 13% bw load swimming bouts (1st 30 s, 2nd to thin), separated by a 30 s interval. The incremental phase of LACmin beginning with initial loads of 4% bw, increased in 0.5% at each 5 min. Peak lactate concentration was collected after 5, 7 and 9 min (mmol L-1) and differed among the protocols P 1 (15.2 +/- 0.4, 14.9 +/- 0.7, 14.8 +/- 0.6) and P2 (14.0 +/- 0.4, 14.9 +/- 0.4, 15.5 +/- 0.5) compared to P3 (5.1 +/- 0.1, 5.6 +/- 0.3, 5.6 +/- 0.3) and P4 (4.7 +/- 0.2, 6.8 +/- 0.2, 7.1 +/- 0.2). The LACmin determination success rates were 58%, 55%, 80% and 91% in P1, P2, P3 and P4 protocols, respectively. The MLSS did not differ from LACmin in any protocol. The LACmin obtained from P4 protocol showed better assurance for the MLSS identification in most of the tested rats. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: hyperlactatemia induction; lactate minimum test; swimming rats